Symposium REAACH 2024 (diségno, 2024)
REAACH 2024 is the fifth edition of the REAACH Symposium (fig. 1), an event that, over the two days of study on October 8 and 9, 2024, featured contributions from international scholars on the topic of the challenges of the discipline of Representation in light of the disruptive and interconnected phenomena of Artificial Intelligence (AI) and eXtended Reality (XR). [read more]